Pemberdayaan Siswa Melalui Instalasi dan Pengelolaan Solar Power Plant di SMPN 04 Tempurejo - Achmad Archam Sya’bana; Fila Ramadhan; Muhammad Rifki Afdillah; Tio Alfian Nirvanto; Jihan Rahfida Haryati; Risse Entikaria Rachmanita (Jurnal Ilmiah Universitas Batanghari Jambi, 2023)
Sunlight as one of the abundant renewable energy sources and can be used as a source of electrical energy, especially in Indonesia which is a tropical country. This community service activity aims to provide solutions to problems experienced by partners, SMPN 04 Tempurejo. The problem experienced by partners is that schools still do not have access to electricity. Methods of implementing community service activities include surveys and observations, socialization, installation preparation, implementation, training and mentoring and evaluation. The results of this community service have run well because all activities carried out are in accordance with the scheduled timeline. The implementation of a 150 Wp solar panel-based electrical energy source at SMPN 04 Tempurejo has succeeded in providing solutions to the problems faced by partners, namely the existence of lighting and new learning media facilities, in the form of mini PCs and increasing students' understanding of renewable energy and its use as an alternative energy source and the use and maintenance of solar panel systems.